Michigan tobacco cessation champions: A rapid qualitative analysis - Devin C. Tomlinson; Chelsea Wilkins; Natalie Bayrakdarian; Frank Dolecki Jr.; Erin E. Bonar; Anne Fernandez; Golfo Tzilos Wernette; Lara N. Coughlin (Preventive Medicine Reports)
Background: Smoking is the leading cause of preventable death in the United States. We interviewed Tobacco Cessation Champions, multi-sector decision makers, across the state of Michigan to assess and identify barriers and facilitators of smoking cessation and the current smoking cessation landscape. Methods: Twenty Tobacco Cessation Champion interviews (n = 20) were completed with multi-sector decision makers to assess implementation barriers and facilitators from May 2022 to September 2023. We used rapid qualitative analysis to identify common themes across the Tobacco Cessation Champion interviews. Results: Three key themes were identified across the Tobacco Cessation Champion interviews: 1) Facilitators and Barriers of Smoking Cessation Efforts; 2) Smoking Cessation Efforts: Underfunded, Underutilized, Not Marketable or Accessible, and 3) Need for more inclusive, person-centered smoking cessation interventions. Conclusion: Across the themes identified in the present report, champions identified myriad areas for improvement in the tobacco cessation landscape, including: Appeal, accessibility, and the functionality of current systems. The community should strive to improve trust and relationships between providers and patients, as the trust established between these parties is imperative for promoting tobacco cessation. Lastly, cessation efforts should aim to address and improve attitudes and stigma toward smoking and tobacco cessation.